If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 5) = -4 Reorder the terms: (5 + x)(x + 5) = -4 Reorder the terms: (5 + x)(5 + x) = -4 Multiply (5 + x) * (5 + x) (5(5 + x) + x(5 + x)) = -4 ((5 * 5 + x * 5) + x(5 + x)) = -4 ((25 + 5x) + x(5 + x)) = -4 (25 + 5x + (5 * x + x * x)) = -4 (25 + 5x + (5x + x2)) = -4 Combine like terms: 5x + 5x = 10x (25 + 10x + x2) = -4 Solving 25 + 10x + x2 = -4 Solving for variable 'x'. Reorder the terms: 25 + 4 + 10x + x2 = -4 + 4 Combine like terms: 25 + 4 = 29 29 + 10x + x2 = -4 + 4 Combine like terms: -4 + 4 = 0 29 + 10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-29' to each side of the equation. 29 + 10x + -29 + x2 = 0 + -29 Reorder the terms: 29 + -29 + 10x + x2 = 0 + -29 Combine like terms: 29 + -29 = 0 0 + 10x + x2 = 0 + -29 10x + x2 = 0 + -29 Combine like terms: 0 + -29 = -29 10x + x2 = -29 The x term is 10x. Take half its coefficient (5). Square it (25) and add it to both sides. Add '25' to each side of the equation. 10x + 25 + x2 = -29 + 25 Reorder the terms: 25 + 10x + x2 = -29 + 25 Combine like terms: -29 + 25 = -4 25 + 10x + x2 = -4 Factor a perfect square on the left side: (x + 5)(x + 5) = -4 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 18-9x=16-8x | | 36=4r+4 | | -3/5r=-9/10 | | 0.45x+0.20(280-x)=77.25 | | 36x^3-12x^2-24x=0 | | 1/2x+4=10 | | 7k-(-3k)+8=0 | | r^2-20x+16=0 | | (x+2/16)=9/18+(x-1/2) | | 6(x+5)/5=2x-3 | | (5y-7)/(3y+1)=5/3 | | -16x+x=-15 | | 0.38-0.66x+0.72x-0.54=0 | | 2*3x-2=14 | | x^2+22x-480=0 | | 1/4x-11 | | 32a-16=4a | | 4-b=1/3(2b+7) | | 15-(5/2)x=9+(1/2)x | | -50=2(v-4) | | 5k-30=3k+15 | | 6+(13-1)/4+2 | | -4y=2x | | 20-4x-2x+6-12x+6=4 | | 4x+7=-4+2x+25 | | 5x+3x=120 | | 0.55x+0.4x=x-2.5 | | 7x+52=2x+12 | | x/8=9/4.5 | | (5t+7)-(2t+7)= | | 12/(x^2+x-2)-(x+3)/(x-1)=(1-x)/(x+2) | | -3=-.5(n-6) |